2020
DOI: 10.5424/sjar/2020183-16255
|View full text |Cite
|
Sign up to set email alerts
|

Soil carbon sequestration and stocks: short-term impact of maize succession to cover crops in Southern Brazil Inceptisol

Abstract: Aim of study: To evaluate soil organic carbon (SOC) sequestration and stock over the succession of maize to winter cover crops under a short-term no-tillage system.Area of study: A subtropical area in Southern Brazil.Material and methods: The experiment was implemented in 2013. The treatments were: seven winter cover crops single cultivated (white-oats, black-oats, annual-ryegrass, canola, vetch, fodder-radish and red-clover); an intercropping (black-oats + vetch); and a fallow, with maize in succession. Soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…However, despite its capacity, the red clover did not develop well in the field, promoting a lower residue input along the years of experiment (Table 2). Locatelli et al (2020) found a similar result for the soil carbon stocks in the same study area, where a stock of ~ 96 mg•ha -1 (0-60 m layer) was obtained for the red clover, against ~ 107 mg•ha -1 (0-60 m layer) for vetch. The same was observed in crops of the brassica's family (fodder radish and canola), despite not biologically fixing N like the legumes, those crops were expected to increase N cycling from deeper layers to the soil surface (Silva et al 2007) and then make it available to maize uptake.…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations
“…However, despite its capacity, the red clover did not develop well in the field, promoting a lower residue input along the years of experiment (Table 2). Locatelli et al (2020) found a similar result for the soil carbon stocks in the same study area, where a stock of ~ 96 mg•ha -1 (0-60 m layer) was obtained for the red clover, against ~ 107 mg•ha -1 (0-60 m layer) for vetch. The same was observed in crops of the brassica's family (fodder radish and canola), despite not biologically fixing N like the legumes, those crops were expected to increase N cycling from deeper layers to the soil surface (Silva et al 2007) and then make it available to maize uptake.…”
Section: Resultssupporting
confidence: 69%
“…This is relevant even in a soil managed in no-tillage system and with high SOM content (44.23 g•dm -3 ), which can supply partially the N demands of maize. However, in the medium to long term, might reduce the soil carbon stocks (Locatelli et al 2020) and therefore, the supply of N to maize. Still, it is necessary to expand the results of the research, with the disclosure not only of the importance of cultivating cover crops instead of fallow to avoid soil degradation, but their relative contribution to plant nutrition and the total or partial replacement of mineral fertilizers, which lowers costs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this way, in the search of a more durable and sustainable option, the use of cover crops has appeared to reduce soil compaction and to promote increases in crop yield (Nicoloso et al, 2008;Blanco-Canqui et al, 2015). Additionally, the management of different crop species with vigorous root system and the addition of adequate amounts of residues, may increase SOM (Locatelli et al, 2020), improve soil physical, chemical and biological quality, promote protection against erosion and maintain the soil moisture (Balota et al, 2014;Frasier et al, 2016).…”
Section: _______________________________________________mentioning
confidence: 99%